Uso de biomasa residual de cascarilla de arroz (Oryza sativa), maíz (Zea mays) y bagazo de caña de azúcar (Saccharum officinarum) y su impacto en la conservación del medio ambiente - Morales Mora, Nathalie Michelle (2024)
The document deals with the use of residual biomass of rice husk (Oryza sativa), corn (Zea mays) and sugarcane bagasse (Saccharum officinarum) and its impact on environmental conservation. The conclusions detail that mainly, the predominant organic components in rice husk are cellulose (39%), hemicellulose (20%) and lignin (22%), representing more than 75% of its mass in the dry state; while the remaining content corresponds to fats and proteins (3.6%). corn includes dry matter 89.50%, crude protein 11.95%, crude fiber 1.53%, neutral detergent fiber 7.55%, acid detergent fiber 3.60%, ash 1.21%, phosphorus 0.26 %, fat 3.43%, starch 68.53%, and total sugars 1.12% and the Sugarcane Bagasse has a cellulose content of 42.91%, a hemicellulose content of 27.92% and a lignin content of 9.74%. Analysis of agricultural charcoal biomass reveals that it contains 29.80% cellulose, 20.61% hemicellulose and 5.70% lignin. Biomass represents a form of sustainable energy that is based on the use of waste of plant origin, such as wood, straw and agricultural waste such as rice husks, corn and sugar cane bagasse, with the purpose of generating energy. in a more environmentally benign manner compared to fossil fuels. Biomass plays a crucial role in conserving forests, promoting rural development and generating electricity.